2020
DOI: 10.13057/biodiv/d210249
|View full text |Cite
|
Sign up to set email alerts
|

Identification of interspecific hybrid between Jatropha curcas × J. integerrima using morphological and molecular markers

Abstract: Abstract. Saptadi D, Asbani N, Heliyanto B, Setiawan A, Sudarsono. 2020. Identification of interspecific hybrid between Jatropha curcas x J. integerrima using morphological and molecular markers. Biodiversitas 21: 814-823. Eight F1 progenies derived from Jatropha curcas × J. integerrima hybridizations were evaluated for their morphological characters and using RAPD, ISSR and SSR markers. Morphological variations among the hybrids were limited and they were intermediate between the Jatropha parents. The eight F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…PCR-based markers have been used extensively in genetic analysis of several plants and are preferable for a number of reasons: requirement of only small quantities of DNA, no DNA blotting required and easy preparation for automation (Nagaraju et al, 2001). Saptadi et al (2020) reported the use of SSR, random amplified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR) markers to confirm interspecific hybrids of J. curcas × J. integerrima. However, there are still very few reports pertaining to interspecific hybrid detection in Jatropha.…”
Section: Introductionmentioning
confidence: 99%
“…PCR-based markers have been used extensively in genetic analysis of several plants and are preferable for a number of reasons: requirement of only small quantities of DNA, no DNA blotting required and easy preparation for automation (Nagaraju et al, 2001). Saptadi et al (2020) reported the use of SSR, random amplified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR) markers to confirm interspecific hybrids of J. curcas × J. integerrima. However, there are still very few reports pertaining to interspecific hybrid detection in Jatropha.…”
Section: Introductionmentioning
confidence: 99%